Simultaneous Occurrence of Rosai–Dorfman Disease and Nodal Marginal Zone Lymphoma in a Patient with Sjögren’s Syndrome - Vadim R. Gorodetskiy; Wolfram Klapper; Natalya A. Probatova; Vladimir I. Vasilyev; Elena V. Rozhnova (Case Reports in Hematology)
We present an exceptionally rare case of co-occurrence of Rosai–Dorfman disease (RDD) and nodal marginal zone lymphoma (NMZL) in a 60-year-old Caucasian female with a 20-year course of Sjögren’s syndrome (SS). In response to treatment for lymphoma, the patient presented a short positive response, followed by a rapid progression of the disease accompanied by the development of the peripheral facial nerve palsy. We failed to detect Epstein–Barr virus (EBV) in the NMZL/RDD sample by EBV-encoded RNA (EBER) in situ hybridization but identified genomic DNA of EBV by polymerase chain reaction. A second biopsy revealed EBV-positive diffuse large B-cell lymphoma (DLBCL), not otherwise specified. The identical clonal immunoglobulin heavy chain gene rearrangements in the NMZL and DLBCL pointed to their clonal relationship. Though the role of EBV in the pathogenesis of some lymphomas is well-known, there have been only few cases of EBV-induced transformation of low-grade B-cell lymphoma into high-grade lymphoma and no cases of a patient with an NMZL background. To our knowledge, this is the first report of a concomitant occurrence of RDD and NMZL in a SS patient.